Evaluación bromatológica y toxicológica de microorganismos específicos en la obtención del ensilaje de banano verde (musa sapientum) - Faubla Zambrano, Ángel Javier (2016)
The objective of this research was to evaluate the bromatological and toxicological factors involved in the ensiling process of green bananas (Musa sapientum) using specific microorganisms. We used the following microorganisms: Bacteria (Lactobacillus plantarum and Bacillus subtilis), yeast (Saccharomyces cerevisiae) and fungus (Trichoderma harzianum). We evaluated the amount of protein, crude fiber, ash, total energy, tannin content, and cost-benefit relationship of the final product. After reception, the raw material went through the processes of selection, washing, cleaning and grating. Subsequently, we prepared the ensiling mix by incorporating 69,3 % green banana, 14,7 % molasses, 16 % water, and 2 % microorganisms. The storage and fermentation processes were completed in a dark place at room temperature for 65 days. Four treatments, using the above-mentioned microorganisms, and an additional control treatment, were evaluated. The treatment with the most appropriate response was A3 (Saccharomyces cerevisiae), showing a 6,91 % and 10,53% of protein and ash increase, respectively. No significant differences between crude fiber and total energy levels were found. Similarly, no significant differences were found among treatments with regard to toxicology, however, all treatments showed values under 0,05 %. Each kilogram of final product inoculated with Saccharomyces cerevisiae has a total cost of $0,36. It was concluded that treatment inoculated with Saccharomyces cerevisiae had the best protein, ash and tannin content as well as a low production cost making it the best treatment.